2012
DOI: 10.17795/jjnpp-4707
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxin M1 Levels in Produced Pasteurized Milk in Ahvaz City by Using HPLC

Abstract: Article type: Original ArticleBackground: Aflatoxins are one of the most potent toxic substances that occur naturally. Nowadays extensive attention has been taken to their existence in food and environment, as there is the possibility of harm to humans following chronic exposure to extremely low levels via food chain. Aflatoxin M1 (AFM 1 ) is a hepatic carcinogenic metabolite found in the milk of lactating animals fed with contaminated feed contaminated by aflatoxin B1 (AFB 1 ).Objectives: This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Competitive traditional biosensing techniques that are already commercially used are, for example, enzyme-linked immunosorbent assay (ELISA) [22], electrochemical sensor [23], bilayer lipid membranes (BLM) [24], high performance liquid chromatography (HPLC) [25,26], micro-electrode immunoassay [27], field immunoassay [28] and surface plasmon resonance spectroscopy (SPR) [29,30]. Compared to those traditional benchtop electrochemical instruments, the main advantages of SOI-based ring resonators are their small size, scalable mass-production and fast readout (real-time) as well as the possibility for low cost, portable devices for point-of-care applications since they rely on CMOS-compatible processes.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive traditional biosensing techniques that are already commercially used are, for example, enzyme-linked immunosorbent assay (ELISA) [22], electrochemical sensor [23], bilayer lipid membranes (BLM) [24], high performance liquid chromatography (HPLC) [25,26], micro-electrode immunoassay [27], field immunoassay [28] and surface plasmon resonance spectroscopy (SPR) [29,30]. Compared to those traditional benchtop electrochemical instruments, the main advantages of SOI-based ring resonators are their small size, scalable mass-production and fast readout (real-time) as well as the possibility for low cost, portable devices for point-of-care applications since they rely on CMOS-compatible processes.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins are toxic compounds, mutagenimmunosuppressive and carcinogen 1 . People in developing countries are at risk ofchronic exposure to aflatoxins through contaminated foods 2 . Among aflatoxins, B1, B2, G1 and G2 are the major toxins.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of AFM1 and CAP in milk has been a concern in some countries, which promotes the emergence of determination of these chemicals using various methods, such as ELISA, HPLC, and immunochromatographic assay. For example, in a previous study [ 12 ], Behfar et al determined 100 samples of pasteurized milk from a local factory, which revealed that the concentration of AFM1 was ranged from 0.45 to 9.760 ng/L, which was below the accepted level (50 ng/L) in milk in Iran. Meanwhile, in a study in which AFM1 levels in samples were analyzed with a commercial competitive ELISA kit and HPLC, the quantification limit was 10 ng/L for ELISA combined with HPLC [ 13 ].…”
Section: Discussionmentioning
confidence: 99%